Fast hash-based high secure hiding technique for digital data security. (16th June 2020) - Shrimali, Shubham; Kumar, Aadarsh; Singh, K. John
In present time, data hiding emerges as one of the important issues in data embedding and security due to the increase of technology. To improve the quality of the video and the security of the data, this paper deals with data hiding technique using proposed SAJ encryption-decryption technique. The data is embedded in different video frames and it is embedded using a cryptographic hash function with a secret key to enhance the security of the data. We also compared different data hiding techniques to ensure the efficiency of algorithm such as codeword substitution, steganography, watermarking, LSB substitution and cryptography. Our focus is to enhance the security, reliability, and to keep the size of the data as low as possible. In this paper, we have proposed new data hiding technique, hash-based high secure hiding technique (HBHSHT) which is more reliable as estimated. It supports a well user-defined level of accessibility and security. As compared different techniques, it is found that the proposed algorithm is more efficient approximately 8%.